2018
DOI: 10.1103/physreve.97.010901
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized oscillations and acoustic fluidization in confined granular materials

Abstract: According to the acoustic fluidization hypothesis, elastic waves at a characteristic frequency form inside seismic faults even in absence of an external perturbation. These waves are able to generate a normal stress which contrasts the confining pressure and promotes failure. Here we study the mechanisms responsible for this wave activation via numerical simulations of a granular fault model. We observe the particles belonging to the percolating backbone, which sustains the stress, to perform synchronized osci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…To drive home the message even further, we now remove the requirement of a smooth tangential force at the Coulomb threshold, allowing the tangential force to reach the limit in an abrupt way. Now the oscillatory instability disappears, since the Hamiltonian (31) remains now valid all the way to the Coulomb threshold. The price is of course that the Jacobian matrix J does not exist since the tangential force is not derivable at the threshold.…”
Section: How Generic Is the Oscillatory Instability?mentioning
confidence: 99%
See 1 more Smart Citation
“…To drive home the message even further, we now remove the requirement of a smooth tangential force at the Coulomb threshold, allowing the tangential force to reach the limit in an abrupt way. Now the oscillatory instability disappears, since the Hamiltonian (31) remains now valid all the way to the Coulomb threshold. The price is of course that the Jacobian matrix J does not exist since the tangential force is not derivable at the threshold.…”
Section: How Generic Is the Oscillatory Instability?mentioning
confidence: 99%
“…These simulations have shown that a granular system may become unstable without any new contact reaching its Coulomb threshold [26]: only after the system becomes unstable and starts slipping new contacts are seen to reach their Coulomb limit. An indirect support towards the existence of collective failure mechanisms also stems from the existence of a linear regime in the response of granular systems to applied perturbations [27][28][29][30][31], which is not easily rationalized assuming failure to originate from an underlying discontinuous process such as the Coulomb failure of a contact.…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify the mechanisms responsible for the activation of these oscillations, the trajectories of each grain inside the stick phase can be monitored in numerical simulations [55]. Because of the high granular density, the large majority of particles is always in contact with their neighbours forming an almost rigid structure, i.e.…”
Section: Mechanisms Producing Af In the Numerical Model Of Seismicmentioning
confidence: 99%
“…In order to identify the mechanisms responsible for the activation of these oscillations, the trajectories of each grain inside the stick phase can be monitored in numerical simulations [55].…”
Section: (Ii) Endogenous Activation Of Acoustic Oscillationsmentioning
confidence: 99%